The manuscript collection of the Scott Polar Research Institute - Savours, Ann (Polar Record, 1959)
The Scott Polar Research Institute possesses a notable collection of manuscripts relating to the polar regions. An appeal through the Press in 1956 resulted in the acquisition of a number of interesting manuscripts which might otherwise have remained unnoticed in store, or been destroyed for want of storage space. The Institute is always anxious to. increase its collection, and is grateful for the gift, or notice of the whereabouts, of any journals, logbooks, letters and other material of polar interest. New accessions are listed in. the annual report of the Scott Polar Research Institute, published in the Polar Record and the Cambridge University Reporter , and are summarized in the Bulletin of the National Register of Archives (London).